A spiritual perspective on Senge's five disciplines: harmony and Alibaba. Issue 6 (7th September 2020) - Mak, Carry; Snell, Robin Stanley; Hong, Jacky
Abstract : Purpose: The purpose of this paper is to investigate Peter Senge's ideas from the perspective of the spiritual ideal of harmony/He (和). Design/methodology/approach: Following a literature review of the conceptualization of Senge's fifth discipline and harmony, an appreciative case study of Alibaba is adopted to demonstrate the role of harmony in guiding the transformative application of the five disciplines of the learning organization. Findings: In developing as a learning organization, Alibaba is portrayed as having embraced three levels of harmony: person-within-oneself, person-to-others and person-to-nature harmony. The authors identify three equivalencies between Senge's disciplines and the traditional Chinese ideal of harmony. First, personal mastery and metal models correspond to developing person-within-oneself harmony. Second, team learning and shared vision entail developing person-to-others harmony. Third, systems thinking aligns with person-to-nature harmony. Practical implications: The case study demonstrates various approaches that can be used to foster the development of person-within-oneself, person-to-others and person-to-nature harmony within an aspiring learning organization. Originality/value: This paper shows how core values of Confucianism, Taoism and Buddhism, distilled into the Chinese ideal of harmony, can encourage the cultivation of learning organizations.